PERAN MEDIA SOSIAL DALAM MENINGKATKAN EFEKTIVITAS PELAYANAN PUBLIK 2024 (Studi Kasus di Dinas Kependudukan dn Pencatatan Sipil Kabupaten Ogan Komering Ulu): Studi Kasus di Dinas Kependudukan dan Pencatatan Sipil Kabupaten Ogan Komering Uu - Unda Listari; Yahnu Wiguno Sanyoto; Eva Susanti (Jurnal Ilmu Pemerintahan, 2025)
This research is entitled "The Role of Social Media in Improving the Effectiveness of Public Services (Case Study at the Population and Civil Registration Office of Ogan Komering Ulu Regency)". The background of this research is based on the importance of utilizing information technology, especially social media, as a means to overcome the challenges of slow, uneven, and less informative public services. This study aims to determine the role of social media in improving the effectiveness of public services, especially in terms of transparency, accountability, public participation, and the balance between community rights and obligations. This research uses a descriptive qualitative approach with data collection techniques through interviews, observation, and documentation. Research informants consisted of OKU Population and Civil Registration Office employees, community service users, and academics. The results show that social media plays a role in accelerating the dissemination of information, facilitating service consultations via WhatsApp, and increasing transparency through content regularly uploaded on Instagram and Facebook. The public feels more helped because they do not need to come in person to simply ask about service flows or document requirements. Social media also provides a space for effective two-way communication between the government and the public. In addition, social media plays a role in educating the public regarding their rights and obligations in population administration. Thus, the use of social media by the Population and Civil Registration Service of Ogan Komering Ulu Regency has significantly contributed to increasing the effectiveness of public services.